MEWASPADAI BENTUK DAN MODUS KECURANGAN MELALUI LAPORAN KEUANGAN - Sururi . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2008)
Financial information which are mainly represented in form of financial statements, are predominant in the decision making process, these are due to the facts that no business and no decisions which are not related to the financial matters. As a consequence the decision makers need reliable financial information to support their decisions otherwise they will commit poor decisions which are harmful to their business and interests. However, in facts very possible that the financial statements fail to present all the important and material facts which are needed by the users, and these matters are happen intentionally due to the existent conflict of interests between the users of the financial statements and the issuer of the financial statements, in this case is management. To overcome these problem the users of financial statements, including independent auditors, must be well informed to the common potentials fraud and misleading financial statements. This paper is aimed to discuss and identify these matters.Keywords: financial statements, independent auditors, potential fraud, misleading financial statements.